2017
DOI: 10.1016/j.neuroimage.2017.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Attentional processes, not implicit mentalizing, mediate performance in a perspective-taking task: Evidence from stimulation of the temporoparietal junction

Abstract: Mentalizing is a fundamental process underpinning human social interaction. Claims of the existence of 'implicit mentalizing' represent a fundamental shift in our understanding of this important skill, suggesting that preverbal infants and even animals may be capable of mentalizing. One of the most influential tasks supporting such claims in adults is the dot perspective-taking task, but demonstrations of similar performance on this task for mentalistic and non-mentalistic stimuli have led to the suggestion th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Specifically in relation to the L1 VPT and director tasks used in the current study, recent work that has tested the domain specificity of these effects and found evidence that similar effects are obtained when the avatar is replaced with an arrow and when the director is replaced with a camera the view of which conditionalizes their responses in the same way as the director (e.g., Santiesteban et al, 2014;Santiesteban et al, 2017;Santiesteban et al, 2015). These results fail to find support for the domain specificity of the effects in the L1 VPT and director tasks, but as illustrated above, there is no necessary link between ToM and domain specificity in accounts of ToM, and plenty of reasons for thinking that domain-general executive functions play central roles in enabling ToM.…”
Section: Limitations In Tom Measures?mentioning
confidence: 60%
See 1 more Smart Citation
“…Specifically in relation to the L1 VPT and director tasks used in the current study, recent work that has tested the domain specificity of these effects and found evidence that similar effects are obtained when the avatar is replaced with an arrow and when the director is replaced with a camera the view of which conditionalizes their responses in the same way as the director (e.g., Santiesteban et al, 2014;Santiesteban et al, 2017;Santiesteban et al, 2015). These results fail to find support for the domain specificity of the effects in the L1 VPT and director tasks, but as illustrated above, there is no necessary link between ToM and domain specificity in accounts of ToM, and plenty of reasons for thinking that domain-general executive functions play central roles in enabling ToM.…”
Section: Limitations In Tom Measures?mentioning
confidence: 60%
“…A further question is whether these tasks actually measure ToM at all, since recent evidence suggests that the processing they entail may not be domain specific to ToM (e.g., Santiesteban et al, 2014;Santiesteban, Kaur, Bird, & Catmur, 2017;Santiesteban, Shah, White, Bird, & Heyes, 2015). There has been longstanding discussion about the extent to which ToM relies upon distinctive cognitive processes.…”
Section: Limitations In Tom Measures?mentioning
confidence: 99%
“…The seminal role of attention in both ToM and EF is plausible on the basis of the abovementioned evidence that the dorsal attention network develops faster than the networks typically recognized to underlie ToM and EF, with connectivity changes between certain networks over the first 2 years of life (Gao et al, 2015). Interestingly, Santiesteban, Kaur, Bird, and Catmur (2017) recently used disruptive TMS over the right TPJ to show that domain-general attentional processes may mediate the ability to take another's visual perspective during selfperspective judgments. Future use of TMS during ToM and EF tasks that vary in their attentional demands may illuminate the degree to which such attentional processes are important in facilitating ToM and EF performance.…”
Section: Summary Limitations and Future Directionsmentioning
confidence: 99%
“…Here, researchers have typically examined whether attentional orienting in response to social gaze and comparison nonsocial cues was associated with differential activations within the attentional control networks . These investigations have also frequently revealed similar neural activity for gaze and arrow cues, with disruptive transcranial magnetic stimulation over the right temporoparietal junction (TPJ) found to modulate the processing of directional information regardless of the social (i.e., a human avatar) or nonsocial (i.e., an arrow) nature of the stimulus . Some work did show cue‐specific modulation—for example results indicating that social, compared with nonsocial, cues elicit stronger and sometimes even unique effects in neural responses—are more effective in guiding infant object processing and learning, and drive behavioral effects that appear more resistant to volitional control .…”
Section: The Three Core Processesmentioning
confidence: 99%